CD56bright natural killer cells induce HBsAg reduction via cytolysis and cccDNA decay in long‐term entecavir‐treated patients switching to peginterferon alfa‐2a. Issue 11 (10th July 2018) - Shi, A.; Zhang, X.; Xiao, F.; Zhu, L.; Yan, W.; Han, M.; Luo, X.; Chen, T.; Ning, Q.
Summary: HBV surface antigen (HBsAg) reduction is well observed in chronic hepatitis B (CHB) patients treated with pegylated interferon alpha‐2a (PegIFNα). However, the mechanism of HBsAg suppression has not been fully elucidated. Twenty‐seven of 55 entecavir‐treated CHB e antigen positive patients were switched to PegIFNα treatment (Group A) whereas 28 patients continued entecavir treatment (Group B). The percentage or absolute number of CD56 bright /CD56 dim NK cells, expression of receptors and cytokines were evaluated by flow cytometry for 48 weeks and correlated with treatment efficacy. In vitro, purified NK cells were co‐cultured with HepAD38 cells for measurement of HBsAg, apoptosis and covalently closed circular DNA (cccDNA). In association with a reduction of HBsAg, the percentage and absolute number of CD56 bright NK cells was significantly elevated in patients in group A, especially in Virologic Responders (VRs, HBsAg decreased). Furthermore, the percentage of NKp30 +, NKp46 +, TRAIL +, TNF‐α + and IFNγ + CD56 bright NK cells were significantly expanded in Group A, which were positively correlated with the decline of HBsAg at week 48. In vitro, peripheral NK cells from Group A induced a decline of HBsAg in comparison with NK cells from Group B which was significantly inhibited by anti‐TRAIL, anti‐TNF‐α and anti‐IFNγ antibodies. Furthermore, apoptosis of HepAD38 cells and levels of cccDNA, were significantly reduced by TRAIL + and TNF‐α + /IFNγ + NK cells from Group A, respectively. A functional restoration of CD56 bright NK cells in entecavir‐treated patients who were switched to PegIFNα contributes to HBsAg and cccDNA clearance through TRAIL‐induced cytolysis and TNF‐α/IFNγ‐mediated noncytolytic pathways.